On a Perpetual State of Becoming: Transnationality and Precarity against the American Dream in Dinaw Mengestu’s The Beautiful Things That Heaven Bears - Rørdal, Henriette (American Studies in Scandinavia, 2025)
This paper reads Ethiopian-American writer Dinaw Mengestu’s The Beautiful Things That Heaven Bears (2007) to consider how the liminal experience of national identity that is often thematized in transnational literature pertains not only to the intersections of race and gender, but also to class conditions. The novel’s protagonist, Sepha, struggles to reconcile idealistic notions of America with the harsh realities of working-class life in a low-income DC neighborhood. To Sepha, citizenship figures not as the stable destination the American dream professes to offer, but rather as a marginal state of isolation and uncertainty. For decades, linear notions of immigration as assimilation have been subject to critique and re-framing. In addition, recent developments in the labor market under late-stage capitalism have generated working-class narratives that are fragmented by the forces of precarity. Mengestu’s novel addresses, through Sepha, an intersection between an ephemeral transnational identity and a precarious working-class position, subverting the narrative chronology of nineteenth- and early twentieth-century migrant novels. By contrast with these, transnational and precarious narratives defer such stable endpoints to remain in transition. The result, this paper argues, is the aesthetic expression of a perpetual state of becoming, the prevalence of which ought to be further considered within the field of American studies.